2002
DOI: 10.3346/jkms.2002.17.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-resistant Aerococcus viridans Bacteremia Associated with Granulocytopenia

Abstract: Aerococcus viridans, a catalase-negative gram-positive coccus rarely causing bacteremia, was isolated from blood cultures of a 52-yr-old man under the granulocytopenic condition. The isolate showed the typical characteristics of A. viridans, i.e., tetrad arrangements in gram stain, positive pyrrolidonyl aminopeptidase (PYR) and negative leucine aminopeptidase (LAP) reactions, and no growth at 45℃. The isolate was revealed to be highly resistant to penicillin, erythromycin, clindamycin, and ceftriaxone, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…Whether the interpretive criteria for streptococci other than S. pneumoniae or those for S. pneumoniae are valid for this genus can be questioned. Most reports describe single isolates or very small numbers of isolates, which indicates that A. viridans has various degrees of susceptibility to penicillin (10,12,15,(17)(18)(19)(20)(21)(22)(23). One report showed that 3 of 29 isolates were resistant (MIC of 0.25) to penicillin (11).…”
mentioning
confidence: 99%
“…Whether the interpretive criteria for streptococci other than S. pneumoniae or those for S. pneumoniae are valid for this genus can be questioned. Most reports describe single isolates or very small numbers of isolates, which indicates that A. viridans has various degrees of susceptibility to penicillin (10,12,15,(17)(18)(19)(20)(21)(22)(23). One report showed that 3 of 29 isolates were resistant (MIC of 0.25) to penicillin (11).…”
mentioning
confidence: 99%
“…8 Granulocytopenia, oral mucositis, history for long-term hospitalization, previous antibiotic use, invasive procedures, and implantations have been defined as primary risk factors for A. viridans related systemic infections. 2,6,7 Although source of contamination could not be clearly determined in the present case, we can say that it is a health-carerelated infection and comorbid immunosuppressive disease have contributed to this infection since he has been receiving hemodialysis for 6 years and had undergone invasive procedure short time ago.…”
Section: Discussionmentioning
confidence: 79%
“…12 Although some authors have reported penicillin-or multidrug-resistant A.viridans strains isolated from clinical specimens, optimal treatment of systemic infections caused by penicillin-resistant A.viridans remains unclear. 2 Approximately half of the patients with infective endocarditis undergo surgical treatment due to severe complications. 13 Each case should be evaluated individually for surgery, and all factors associated with risk enhancement should be identified at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Aerococci have been isolated from the environment as well as foods 1,2 because they can cause diseases in crustaceans 3 and animals. 4 A. viridans also occasionally causes systemic infections in immunocompromised hosts, including meningitis, 5 urinary tract infections, 6 osteomyelitis, 7 septic arthritis, wound infection, 8 and, most commonly, bacteremia and endocarditis. 1,7,9e11 Risk factors for infection have not been fully identified; but, granulocytopenia, oral mucositis, prolonged hospitalization, previous treatment with antibiotics, invasive procedures, and implantation of foreign bodies have been described as the major risk factors related to A. viridans systemic infection.…”
Section: Introductionmentioning
confidence: 99%